Analisis Prediksi Finansial Distress dengan Metode Altman Z-Score dan Springate Sebelum dan Selama Covid- 19 - Fauziah Rahman (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research aims to predict financial distress in property and real estate sector companies, before and during the pandemic of Covid-19  using the Altman Z'-Score and Sprigate S-Score ratio analysis. The population of this research is all property and real estate companies listed on the Indonesian Stock Exchange for the period 2018 to 2020, so the population of this study is 66 companies. The sample was selected based on predetermined purposive sampling criteria. Those selected according to the specified sample criteria were 44 companies. The data analysis technique used the Altman Z-Score and Springate S-Score discriminant analysis techniques. The results of this study indicate an increase in the number of companies in the distressed category (red zone) during the COVID-19 pandemic (in 2020) by 16%, which was twice as high as before the Covid-19 pandemic, which was 7%. This indicates that there are difficulties both financially and in liquidity as well as a decrease in the company's ability to grow, which may lead to bankruptcy.